A interação nas distâncias: a análise de um processo - Meirelles, Cláudia de Souza Cardoso (2010)
Education and technology have always walked side by side. The Information and Communication Technologies are inserted in education as a profile of people from the new era. This research has the objective of understanding the insertion of the use of the Technologies of Information and Communication within the educational context, from the analysis of the process of interactivity among students and teachers of the Portuguese distance course of the Tiradentes University (Unit). For such, the empiric investigation was based on the analysis of academic documents, such as: the Course Pedagogical Project and Class Planning of regular classes, in regular classrooms, as well as interviews, focal groups, and pictures with people who live the history of the course. Direct observations were also conducted. The methodology applied was bibliographic and qualitative research of the exploratory type, using the information that was collected through the interviews. The results of this research demonstrated that the interaction promoted by the ICT represents a process of social change, and therefore, of development for education. It was concluded that the Distance Education has to overcome some fragilities, aiming at contributing to the educational field and to the promotion of interactions among students